[Ekslibris] J[ørgen] L[indhardt] R[asmussen] [Zbigniew Dolatowski]. - Dolatowski, Zbigniew (1927-2001) (1972)
Przedstawia ilustrację do bajki o świniopasie. U dołu inicjały: J. L. R. Pod wyobrażeniem ołówkiem autograf aut. i data.